2013
DOI: 10.2460/javma.242.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic findings in dogs and cats with temporomandibular joint disorders: 58 cases (2006–2011)

Abstract: Objective To describe CT findings in dogs and cats with temporomandibular joint (TMJ) disorders. Design Retrospective case-series. Animals 41 dogs and 17 cats. Procedures Medical records and CT images of the skull were reviewed for dogs and cats that were examined at a dentistry and oral surgery specialty practice between 2006 and 2011. Results Of 142 dogs and 42 cats evaluated, 41 dogs and 17 cats had CT findings consistent with a TMJ disorder. In dogs, the most common TMJ disorder was osteoarthritis;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
137
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(152 citation statements)
references
References 41 publications
(61 reference statements)
13
137
1
1
Order By: Relevance
“…16,31 Importantly, and in correlation with the finding of the present study, TMJ-OA was found to be the most common disease entity of the TMJ of the domestic dog. 16 In addition, in a human autopsy study macroscopic or microscopic evidence of TMJ-OA in 56% of middle-age to old individuals was found.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…16,31 Importantly, and in correlation with the finding of the present study, TMJ-OA was found to be the most common disease entity of the TMJ of the domestic dog. 16 In addition, in a human autopsy study macroscopic or microscopic evidence of TMJ-OA in 56% of middle-age to old individuals was found.…”
Section: Discussionsupporting
confidence: 83%
“…15 In a recent study, we demonstrated that TMJ-OA is the major TMJ disorder in the domestic dog and cat; however, occurring in concert with other TMJ disorders such as dysplasia, trauma, luxation, neoplasia, and masticatory muscle disorders. 16 The disease also occurs in southern sea otters (Enhydra lutris nereis) but in low frequency without significant association between age and sex with the presence or severity of TMJ-OA. 9 California sea lions are members of family Otariidae ('eared seals').…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Osteoarthritis is reported to be the most common disease associated with the TMJ and is also present is sea otters. 10,[16][17][18][19] However, the causes of TMJ osteoarthritis (TMJ-OA) are unclear and may have complex pathophysiology with a multitude of risk factors. 20 It can either be primary or secondary to trauma, abnormal morphology, or other acute or chronic overload situations.…”
Section: Discussionmentioning
confidence: 99%
“…A series of papers has been published on dental and TMJ pathology of marine mammal species: the northern elephant seal (M. angustirostris) (Abbott and Verstraete, 2005), the southern sea otter (Enhydra lutris nereis) (Arzi et al, 2013a;Winer et al, 2013), the California sea lion (Zalophus californianus) (Sinai et al, 2014;Arzi et al, 2015), the northern fur seal (Callorhinus ursinus) (Aalderink et al, 2015a) and the eastern Pacific harbour seal (Phoca vitulina richardii) (Aalderink et al, 2015b). In general, museum collections of skulls, such as those making up the aforementioned studies and this study, are obtained from strandings, carcass recovery and donations by rehabilitation centres.…”
Section: Introductionmentioning
confidence: 99%